Eugenics, Race and Canada’s First-Wave Feminists: Dis/Abling the Debates - de la Cour, Lykke (Atlantis, 2017)
Using government reports produced by one of Ontario’s pioneering women physicians and leading eugenic crusaders, Dr. Helen MacMurchy, this article interrogates the significance of disability as a central paradigm within first-wave feminism and its promotion of eugenic reforms. I examine how conceptualizations of race were reconstituted through the construct of disability to generate not only inter- but also intra-racial distinctions between differently classed white women. I argue that it was ultimately by leveraging a range of social categories —gender, class, race, and transgressive forms of sexuality—into a disabling paradigm that not only racialized women, but also poor white women were disempowered by eugenics.